Acinetobacter spp. Coinfection with Elizabethkingia meningoseptica: A Case Report at a Referral Hospital in Iran - Kobra Salimiyan Rizi; Hadi Farsiani; Saeid Amel Jamehdar; Mahboubeh Mohammadzadeh (Reviews in Clinical Medicine, 2019)
Elizabethkingia meningoseptica is an emerging nosocomial gram-negative, rod-shaped pathogen in patients with underlying diseases. This bacterium is also considered to be a major pathogen in hospitalized patients. Some of the main risk factors for E. meningosepticum infections include immunosuppression (e.g., end-stage hepatic and renal diseases) and prematurity in neonates. Furthermore, E. meningosepticum could cause pneumonia, endocarditis, and bacteremia in adults. The uncommon resistance pattern of this bacterium, as well as its intrinsic resistance to colistin, makes the treatment of the associated infections challenging unless the susceptibility patterns are available. In this article, we have presented the first case of pulmonary coinfection with multidrug-resistant (MDR) Acinetobacter spp. and E. meningoseptica in Iran. A 20-year-old female patient was admitted to our hospital with tetralogy of fallot as an underlying disease since childhood. The patient underwent cardiac surgery. On the third postoperative day (POD), the patient developed lung infection and left-lung collapse. Antibiotic therapy was initiated for MDR Acinetobacter spp. obtained from her primary culture of tracheal discharges. When fever persisted in the patient, the secondary culture of her tracheal discharges was observed to be positive for E. meningoseptica. In this case report, no clinical correlations were observed between the E. meningoseptica isolated from respiratory secretions and the primary respiratory infection, suggesting that E. meningoseptica is an indicator of severe underlying diseases rather than an actual pathogen.